Treatment of large renal allograft arterial pseudoaneurysm with in situ cold perfusion, ex vivo vascular reconstruction and reimplantation - Brent Taiting Xia; Aleksandr Aleksandrovich Reznichenko; Madison Colyn Cuffy; Ervin Steve Woodle (Society of Diabetic Nephropathy Prevention, 2019)
Background: Pseudoaneurysm after renal transplantation is a rare but serious complication. Case Presentation: We report a case of a 76-year-old man who presented six weeks after kidney transplant with a large pseudoaneurysm arising from the renal artery anastomosis, causing renal vein compression and renal allograft dysfunction. Prior to the removal of the transplanted kidney, an in situ cold perfusion of the allograft was performed. The pseudoaneurysm was repaired ex vivo and the renal artery was reconstructed. External iliac vein was reconstructed with deceased donor interposition allograft, and the kidney was then re-implanted. The patient recovered with immediate allograft function. Conclusions: Successful surgical management of a large renal allograft arterial pseudoaneurysm involves avoidance of dissection of the pseudoaneurysm, utilization of in situ cold perfusion and en-bloc removal of the kidney together with pseudoaneurysm, and pseudoaneurysm incision and vascular bypass reconstruction ex vivo